The The Effectiveness of Using Webtoon Platform on Students’ Reading Comprehension to First Grade at SMA Negeri 1 Halmahera Tengah - Wanti Misnayanti Taslim; Amrin Hi. Saban; Nurlaily Sofyan (English Education Department, Faculty of Education Muhammadiyah University of North Maluku, 2022)
The objective of research to find out the effectiveness of using webtoon platform on students’ reading comprehension to the first grade at SMA Negeri 1 Halmahera Tengah. This research used quantitative method by using non-equivalent control group design. The research was conducted at SMA Negeri 1 Halmahera Tengah involving 50 students in the first grade as a sample and it selected by stratified random sampling. The procedure of data collection are; pretest, treatment, and posttest by using test items as an instrument of the study. The pretest was carried out before learning by using questions that had been prepared by the researchers. After the pretest, it did a learning process (treatment) through webtoon platform. Then a posttest was carried out after the treatment was carried out for four meetings.All data collection was analyzed using descriptive and inferential analysis data such as normality test, homogeneity test and independent sample T-test to compare the results of the pretest and post-test with a significant level of 5%. The results of the study showed (1)students' reading comprehension before treatment was lower, (2) webtoon platform made a very significant contribution to students' reading comprehension, (3) The null hypothesis stated that webtoon platform did not have an effective to improving students' reading comprehension was rejected and the alternative hypothesis was accepted, and(4) the webtoon platform not only contributed to improve students’ reading comprehension in English text, but it also one way alternative media that can be used in teaching proses.